4.10: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|-  
|-  
| [https://dlmf.nist.gov/4.10.E1 4.10.E1] || [[Item:Q1616|<math>\int\frac{\diff{z}}{z} = \ln@@{z}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int\frac{\diff{z}}{z} = \ln@@{z}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((1)/(z), z) = ln(z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[1,z], z, GenerateConditions->None] == Log[z]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 7]
| [https://dlmf.nist.gov/4.10.E1 4.10.E1] || <math qid="Q1616">\int\frac{\diff{z}}{z} = \ln@@{z}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int\frac{\diff{z}}{z} = \ln@@{z}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((1)/(z), z) = ln(z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[1,z], z, GenerateConditions->None] == Log[z]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 7]
|-  
|-  
| [https://dlmf.nist.gov/4.10.E2 4.10.E2] || [[Item:Q1617|<math>\int\ln@@{z}\diff{z} = z\ln@@{z}-z</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int\ln@@{z}\diff{z} = z\ln@@{z}-z</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int(ln(z), z) = z*ln(z)- z</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Log[z], z, GenerateConditions->None] == z*Log[z]- z</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 7]
| [https://dlmf.nist.gov/4.10.E2 4.10.E2] || <math qid="Q1617">\int\ln@@{z}\diff{z} = z\ln@@{z}-z</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int\ln@@{z}\diff{z} = z\ln@@{z}-z</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int(ln(z), z) = z*ln(z)- z</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Log[z], z, GenerateConditions->None] == z*Log[z]- z</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 7]
|-  
|-  
| [https://dlmf.nist.gov/4.10.E3 4.10.E3] || [[Item:Q1618|<math>\int z^{n}\ln@@{z}\diff{z} = \frac{z^{n+1}}{n+1}\ln@@{z}-\frac{z^{n+1}}{(n+1)^{2}}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int z^{n}\ln@@{z}\diff{z} = \frac{z^{n+1}}{n+1}\ln@@{z}-\frac{z^{n+1}}{(n+1)^{2}}</syntaxhighlight> || <math>n \neq -1</math> || <syntaxhighlight lang=mathematica>int((z)^(n)* ln(z), z) = ((z)^(n + 1))/(n + 1)*ln(z)-((z)^(n + 1))/((n + 1)^(2))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[(z)^(n)* Log[z], z, GenerateConditions->None] == Divide[(z)^(n + 1),n + 1]*Log[z]-Divide[(z)^(n + 1),(n + 1)^(2)]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 21]
| [https://dlmf.nist.gov/4.10.E3 4.10.E3] || <math qid="Q1618">\int z^{n}\ln@@{z}\diff{z} = \frac{z^{n+1}}{n+1}\ln@@{z}-\frac{z^{n+1}}{(n+1)^{2}}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int z^{n}\ln@@{z}\diff{z} = \frac{z^{n+1}}{n+1}\ln@@{z}-\frac{z^{n+1}}{(n+1)^{2}}</syntaxhighlight> || <math>n \neq -1</math> || <syntaxhighlight lang=mathematica>int((z)^(n)* ln(z), z) = ((z)^(n + 1))/(n + 1)*ln(z)-((z)^(n + 1))/((n + 1)^(2))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[(z)^(n)* Log[z], z, GenerateConditions->None] == Divide[(z)^(n + 1),n + 1]*Log[z]-Divide[(z)^(n + 1),(n + 1)^(2)]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 21]
|-  
|-  
| [https://dlmf.nist.gov/4.10.E4 4.10.E4] || [[Item:Q1619|<math>\int\frac{\diff{z}}{z\ln@@{z}} = \ln@{\ln@@{z}}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int\frac{\diff{z}}{z\ln@@{z}} = \ln@{\ln@@{z}}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((1)/(z*ln(z)), z) = ln(ln(z))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[1,z*Log[z]], z, GenerateConditions->None] == Log[Log[z]]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 7]
| [https://dlmf.nist.gov/4.10.E4 4.10.E4] || <math qid="Q1619">\int\frac{\diff{z}}{z\ln@@{z}} = \ln@{\ln@@{z}}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int\frac{\diff{z}}{z\ln@@{z}} = \ln@{\ln@@{z}}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((1)/(z*ln(z)), z) = ln(ln(z))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[1,z*Log[z]], z, GenerateConditions->None] == Log[Log[z]]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 7]
|-  
|-  
| [https://dlmf.nist.gov/4.10.E5 4.10.E5] || [[Item:Q1620|<math>\int_{0}^{1}\frac{\ln@@{t}}{1-t}\diff{t} = -\frac{\pi^{2}}{6}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{1}\frac{\ln@@{t}}{1-t}\diff{t} = -\frac{\pi^{2}}{6}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((ln(t))/(1 - t), t = 0..1) = -((Pi)^(2))/(6)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[Log[t],1 - t], {t, 0, 1}, GenerateConditions->None] == -Divide[(Pi)^(2),6]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 1]
| [https://dlmf.nist.gov/4.10.E5 4.10.E5] || <math qid="Q1620">\int_{0}^{1}\frac{\ln@@{t}}{1-t}\diff{t} = -\frac{\pi^{2}}{6}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{1}\frac{\ln@@{t}}{1-t}\diff{t} = -\frac{\pi^{2}}{6}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((ln(t))/(1 - t), t = 0..1) = -((Pi)^(2))/(6)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[Log[t],1 - t], {t, 0, 1}, GenerateConditions->None] == -Divide[(Pi)^(2),6]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 1]
|-  
|-  
| [https://dlmf.nist.gov/4.10.E6 4.10.E6] || [[Item:Q1621|<math>\int_{0}^{1}\frac{\ln@@{t}}{1+t}\diff{t} = -\frac{\pi^{2}}{12}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{1}\frac{\ln@@{t}}{1+t}\diff{t} = -\frac{\pi^{2}}{12}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((ln(t))/(1 + t), t = 0..1) = -((Pi)^(2))/(12)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[Log[t],1 + t], {t, 0, 1}, GenerateConditions->None] == -Divide[(Pi)^(2),12]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 1]
| [https://dlmf.nist.gov/4.10.E6 4.10.E6] || <math qid="Q1621">\int_{0}^{1}\frac{\ln@@{t}}{1+t}\diff{t} = -\frac{\pi^{2}}{12}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{1}\frac{\ln@@{t}}{1+t}\diff{t} = -\frac{\pi^{2}}{12}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((ln(t))/(1 + t), t = 0..1) = -((Pi)^(2))/(12)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[Log[t],1 + t], {t, 0, 1}, GenerateConditions->None] == -Divide[(Pi)^(2),12]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 1]
|-  
|-  
| [https://dlmf.nist.gov/4.10.E8 4.10.E8] || [[Item:Q1623|<math>\int e^{az}\diff{z} = \frac{e^{az}}{a}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int e^{az}\diff{z} = \frac{e^{az}}{a}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int(exp(a*z), z) = (exp(a*z))/(a)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Exp[a*z], z, GenerateConditions->None] == Divide[Exp[a*z],a]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 42]
| [https://dlmf.nist.gov/4.10.E8 4.10.E8] || <math qid="Q1623">\int e^{az}\diff{z} = \frac{e^{az}}{a}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int e^{az}\diff{z} = \frac{e^{az}}{a}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int(exp(a*z), z) = (exp(a*z))/(a)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Exp[a*z], z, GenerateConditions->None] == Divide[Exp[a*z],a]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 42]
|-  
|-  
| [https://dlmf.nist.gov/4.10.E9 4.10.E9] || [[Item:Q1624|<math>\int\frac{\diff{z}}{e^{az}+b} = \frac{1}{ab}(az-\ln@{e^{az}+b})</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int\frac{\diff{z}}{e^{az}+b} = \frac{1}{ab}(az-\ln@{e^{az}+b})</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((1)/(exp(a*z)+ b), z) = (1)/(a*b)*(a*z - ln(exp(a*z)+ b))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[1,Exp[a*z]+ b], z, GenerateConditions->None] == Divide[1,a*b]*(a*z - Log[Exp[a*z]+ b])</syntaxhighlight> || Failure || Successful || Successful [Tested: 252] || Successful [Tested: 252]
| [https://dlmf.nist.gov/4.10.E9 4.10.E9] || <math qid="Q1624">\int\frac{\diff{z}}{e^{az}+b} = \frac{1}{ab}(az-\ln@{e^{az}+b})</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int\frac{\diff{z}}{e^{az}+b} = \frac{1}{ab}(az-\ln@{e^{az}+b})</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((1)/(exp(a*z)+ b), z) = (1)/(a*b)*(a*z - ln(exp(a*z)+ b))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[1,Exp[a*z]+ b], z, GenerateConditions->None] == Divide[1,a*b]*(a*z - Log[Exp[a*z]+ b])</syntaxhighlight> || Failure || Successful || Successful [Tested: 252] || Successful [Tested: 252]
|-  
|-  
| [https://dlmf.nist.gov/4.10.E10 4.10.E10] || [[Item:Q1625|<math>\int\frac{e^{az}-1}{e^{az}+1}\diff{z} = \frac{2}{a}\ln@{e^{az/2}+e^{-az/2}}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int\frac{e^{az}-1}{e^{az}+1}\diff{z} = \frac{2}{a}\ln@{e^{az/2}+e^{-az/2}}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((exp(a*z)- 1)/(exp(a*z)+ 1), z) = (2)/(a)*ln(exp(a*z/2)+ exp(- a*z/2))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[Exp[a*z]- 1,Exp[a*z]+ 1], z, GenerateConditions->None] == Divide[2,a]*Log[Exp[a*z/2]+ Exp[- a*z/2]]</syntaxhighlight> || Failure || Failure || Successful [Tested: 42] || Successful [Tested: 42]
| [https://dlmf.nist.gov/4.10.E10 4.10.E10] || <math qid="Q1625">\int\frac{e^{az}-1}{e^{az}+1}\diff{z} = \frac{2}{a}\ln@{e^{az/2}+e^{-az/2}}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int\frac{e^{az}-1}{e^{az}+1}\diff{z} = \frac{2}{a}\ln@{e^{az/2}+e^{-az/2}}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((exp(a*z)- 1)/(exp(a*z)+ 1), z) = (2)/(a)*ln(exp(a*z/2)+ exp(- a*z/2))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[Exp[a*z]- 1,Exp[a*z]+ 1], z, GenerateConditions->None] == Divide[2,a]*Log[Exp[a*z/2]+ Exp[- a*z/2]]</syntaxhighlight> || Failure || Failure || Successful [Tested: 42] || Successful [Tested: 42]
|-  
|-  
| [https://dlmf.nist.gov/4.10.E11 4.10.E11] || [[Item:Q1626|<math>\int_{-\infty}^{\infty}e^{-cx^{2}}\diff{x} = \sqrt{\frac{\pi}{c}}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{-\infty}^{\infty}e^{-cx^{2}}\diff{x} = \sqrt{\frac{\pi}{c}}</syntaxhighlight> || <math>\realpart@@{c} > 0</math> || <syntaxhighlight lang=mathematica>int(exp(- c*(x)^(2)), x = - infinity..infinity) = sqrt((Pi)/(c))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Exp[- c*(x)^(2)], {x, - Infinity, Infinity}, GenerateConditions->None] == Sqrt[Divide[Pi,c]]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 3]
| [https://dlmf.nist.gov/4.10.E11 4.10.E11] || <math qid="Q1626">\int_{-\infty}^{\infty}e^{-cx^{2}}\diff{x} = \sqrt{\frac{\pi}{c}}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{-\infty}^{\infty}e^{-cx^{2}}\diff{x} = \sqrt{\frac{\pi}{c}}</syntaxhighlight> || <math>\realpart@@{c} > 0</math> || <syntaxhighlight lang=mathematica>int(exp(- c*(x)^(2)), x = - infinity..infinity) = sqrt((Pi)/(c))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Exp[- c*(x)^(2)], {x, - Infinity, Infinity}, GenerateConditions->None] == Sqrt[Divide[Pi,c]]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 3]
|-  
|-  
| [https://dlmf.nist.gov/4.10.E12 4.10.E12] || [[Item:Q1627|<math>\int_{0}^{\ln@@{2}}\frac{xe^{x}}{e^{x}-1}\diff{x} = \frac{\pi^{2}}{12}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{\ln@@{2}}\frac{xe^{x}}{e^{x}-1}\diff{x} = \frac{\pi^{2}}{12}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((x*exp(x))/(exp(x)- 1), x = 0..ln(2)) = ((Pi)^(2))/(12)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[x*Exp[x],Exp[x]- 1], {x, 0, Log[2]}, GenerateConditions->None] == Divide[(Pi)^(2),12]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 1]
| [https://dlmf.nist.gov/4.10.E12 4.10.E12] || <math qid="Q1627">\int_{0}^{\ln@@{2}}\frac{xe^{x}}{e^{x}-1}\diff{x} = \frac{\pi^{2}}{12}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{\ln@@{2}}\frac{xe^{x}}{e^{x}-1}\diff{x} = \frac{\pi^{2}}{12}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((x*exp(x))/(exp(x)- 1), x = 0..ln(2)) = ((Pi)^(2))/(12)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[x*Exp[x],Exp[x]- 1], {x, 0, Log[2]}, GenerateConditions->None] == Divide[(Pi)^(2),12]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 1]
|-  
|-  
| [https://dlmf.nist.gov/4.10.E13 4.10.E13] || [[Item:Q1628|<math>\int_{0}^{\infty}\frac{\diff{x}}{e^{x}+1} = \ln@@{2}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{\infty}\frac{\diff{x}}{e^{x}+1} = \ln@@{2}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((1)/(exp(x)+ 1), x = 0..infinity) = ln(2)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[1,Exp[x]+ 1], {x, 0, Infinity}, GenerateConditions->None] == Log[2]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 1]
| [https://dlmf.nist.gov/4.10.E13 4.10.E13] || <math qid="Q1628">\int_{0}^{\infty}\frac{\diff{x}}{e^{x}+1} = \ln@@{2}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\int_{0}^{\infty}\frac{\diff{x}}{e^{x}+1} = \ln@@{2}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>int((1)/(exp(x)+ 1), x = 0..infinity) = ln(2)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Integrate[Divide[1,Exp[x]+ 1], {x, 0, Infinity}, GenerateConditions->None] == Log[2]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 1]
|}
|}
</div>
</div>

Latest revision as of 11:05, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
4.10.E1 d z z = ln z 𝑧 𝑧 𝑧 {\displaystyle{\displaystyle\int\frac{\mathrm{d}z}{z}=\ln z}}
\int\frac{\diff{z}}{z} = \ln@@{z}

int((1)/(z), z) = ln(z)
Integrate[Divide[1,z], z, GenerateConditions->None] == Log[z]
Successful Successful - Successful [Tested: 7]
4.10.E2 ln z d z = z ln z - z 𝑧 𝑧 𝑧 𝑧 𝑧 {\displaystyle{\displaystyle\int\ln z\mathrm{d}z=z\ln z-z}}
\int\ln@@{z}\diff{z} = z\ln@@{z}-z

int(ln(z), z) = z*ln(z)- z
Integrate[Log[z], z, GenerateConditions->None] == z*Log[z]- z
Successful Successful - Successful [Tested: 7]
4.10.E3 z n ln z d z = z n + 1 n + 1 ln z - z n + 1 ( n + 1 ) 2 superscript 𝑧 𝑛 𝑧 𝑧 superscript 𝑧 𝑛 1 𝑛 1 𝑧 superscript 𝑧 𝑛 1 superscript 𝑛 1 2 {\displaystyle{\displaystyle\int z^{n}\ln z\mathrm{d}z=\frac{z^{n+1}}{n+1}\ln z% -\frac{z^{n+1}}{(n+1)^{2}}}}
\int z^{n}\ln@@{z}\diff{z} = \frac{z^{n+1}}{n+1}\ln@@{z}-\frac{z^{n+1}}{(n+1)^{2}}
n - 1 𝑛 1 {\displaystyle{\displaystyle n\neq-1}}
int((z)^(n)* ln(z), z) = ((z)^(n + 1))/(n + 1)*ln(z)-((z)^(n + 1))/((n + 1)^(2))
Integrate[(z)^(n)* Log[z], z, GenerateConditions->None] == Divide[(z)^(n + 1),n + 1]*Log[z]-Divide[(z)^(n + 1),(n + 1)^(2)]
Successful Successful - Successful [Tested: 21]
4.10.E4 d z z ln z = ln ( ln z ) 𝑧 𝑧 𝑧 𝑧 {\displaystyle{\displaystyle\int\frac{\mathrm{d}z}{z\ln z}=\ln\left(\ln z% \right)}}
\int\frac{\diff{z}}{z\ln@@{z}} = \ln@{\ln@@{z}}

int((1)/(z*ln(z)), z) = ln(ln(z))
Integrate[Divide[1,z*Log[z]], z, GenerateConditions->None] == Log[Log[z]]
Successful Successful - Successful [Tested: 7]
4.10.E5 0 1 ln t 1 - t d t = - π 2 6 superscript subscript 0 1 𝑡 1 𝑡 𝑡 superscript 𝜋 2 6 {\displaystyle{\displaystyle\int_{0}^{1}\frac{\ln t}{1-t}\mathrm{d}t=-\frac{% \pi^{2}}{6}}}
\int_{0}^{1}\frac{\ln@@{t}}{1-t}\diff{t} = -\frac{\pi^{2}}{6}

int((ln(t))/(1 - t), t = 0..1) = -((Pi)^(2))/(6)
Integrate[Divide[Log[t],1 - t], {t, 0, 1}, GenerateConditions->None] == -Divide[(Pi)^(2),6]
Successful Successful - Successful [Tested: 1]
4.10.E6 0 1 ln t 1 + t d t = - π 2 12 superscript subscript 0 1 𝑡 1 𝑡 𝑡 superscript 𝜋 2 12 {\displaystyle{\displaystyle\int_{0}^{1}\frac{\ln t}{1+t}\mathrm{d}t=-\frac{% \pi^{2}}{12}}}
\int_{0}^{1}\frac{\ln@@{t}}{1+t}\diff{t} = -\frac{\pi^{2}}{12}

int((ln(t))/(1 + t), t = 0..1) = -((Pi)^(2))/(12)
Integrate[Divide[Log[t],1 + t], {t, 0, 1}, GenerateConditions->None] == -Divide[(Pi)^(2),12]
Successful Successful - Successful [Tested: 1]
4.10.E8 e a z d z = e a z a superscript 𝑒 𝑎 𝑧 𝑧 superscript 𝑒 𝑎 𝑧 𝑎 {\displaystyle{\displaystyle\int e^{az}\mathrm{d}z=\frac{e^{az}}{a}}}
\int e^{az}\diff{z} = \frac{e^{az}}{a}

int(exp(a*z), z) = (exp(a*z))/(a)
Integrate[Exp[a*z], z, GenerateConditions->None] == Divide[Exp[a*z],a]
Successful Successful - Successful [Tested: 42]
4.10.E9 d z e a z + b = 1 a b ( a z - ln ( e a z + b ) ) 𝑧 superscript 𝑒 𝑎 𝑧 𝑏 1 𝑎 𝑏 𝑎 𝑧 superscript 𝑒 𝑎 𝑧 𝑏 {\displaystyle{\displaystyle\int\frac{\mathrm{d}z}{e^{az}+b}=\frac{1}{ab}(az-% \ln\left(e^{az}+b\right))}}
\int\frac{\diff{z}}{e^{az}+b} = \frac{1}{ab}(az-\ln@{e^{az}+b})

int((1)/(exp(a*z)+ b), z) = (1)/(a*b)*(a*z - ln(exp(a*z)+ b))
Integrate[Divide[1,Exp[a*z]+ b], z, GenerateConditions->None] == Divide[1,a*b]*(a*z - Log[Exp[a*z]+ b])
Failure Successful Successful [Tested: 252] Successful [Tested: 252]
4.10.E10 e a z - 1 e a z + 1 d z = 2 a ln ( e a z / 2 + e - a z / 2 ) superscript 𝑒 𝑎 𝑧 1 superscript 𝑒 𝑎 𝑧 1 𝑧 2 𝑎 superscript 𝑒 𝑎 𝑧 2 superscript 𝑒 𝑎 𝑧 2 {\displaystyle{\displaystyle\int\frac{e^{az}-1}{e^{az}+1}\mathrm{d}z=\frac{2}{% a}\ln\left(e^{az/2}+e^{-az/2}\right)}}
\int\frac{e^{az}-1}{e^{az}+1}\diff{z} = \frac{2}{a}\ln@{e^{az/2}+e^{-az/2}}

int((exp(a*z)- 1)/(exp(a*z)+ 1), z) = (2)/(a)*ln(exp(a*z/2)+ exp(- a*z/2))
Integrate[Divide[Exp[a*z]- 1,Exp[a*z]+ 1], z, GenerateConditions->None] == Divide[2,a]*Log[Exp[a*z/2]+ Exp[- a*z/2]]
Failure Failure Successful [Tested: 42] Successful [Tested: 42]
4.10.E11 - e - c x 2 d x = π c superscript subscript superscript 𝑒 𝑐 superscript 𝑥 2 𝑥 𝜋 𝑐 {\displaystyle{\displaystyle\int_{-\infty}^{\infty}e^{-cx^{2}}\mathrm{d}x=% \sqrt{\frac{\pi}{c}}}}
\int_{-\infty}^{\infty}e^{-cx^{2}}\diff{x} = \sqrt{\frac{\pi}{c}}
c > 0 𝑐 0 {\displaystyle{\displaystyle\Re c>0}}
int(exp(- c*(x)^(2)), x = - infinity..infinity) = sqrt((Pi)/(c))
Integrate[Exp[- c*(x)^(2)], {x, - Infinity, Infinity}, GenerateConditions->None] == Sqrt[Divide[Pi,c]]
Successful Successful - Successful [Tested: 3]
4.10.E12 0 ln 2 x e x e x - 1 d x = π 2 12 superscript subscript 0 2 𝑥 superscript 𝑒 𝑥 superscript 𝑒 𝑥 1 𝑥 superscript 𝜋 2 12 {\displaystyle{\displaystyle\int_{0}^{\ln 2}\frac{xe^{x}}{e^{x}-1}\mathrm{d}x=% \frac{\pi^{2}}{12}}}
\int_{0}^{\ln@@{2}}\frac{xe^{x}}{e^{x}-1}\diff{x} = \frac{\pi^{2}}{12}

int((x*exp(x))/(exp(x)- 1), x = 0..ln(2)) = ((Pi)^(2))/(12)
Integrate[Divide[x*Exp[x],Exp[x]- 1], {x, 0, Log[2]}, GenerateConditions->None] == Divide[(Pi)^(2),12]
Successful Successful - Successful [Tested: 1]
4.10.E13 0 d x e x + 1 = ln 2 superscript subscript 0 𝑥 superscript 𝑒 𝑥 1 2 {\displaystyle{\displaystyle\int_{0}^{\infty}\frac{\mathrm{d}x}{e^{x}+1}=\ln 2}}
\int_{0}^{\infty}\frac{\diff{x}}{e^{x}+1} = \ln@@{2}

int((1)/(exp(x)+ 1), x = 0..infinity) = ln(2)
Integrate[Divide[1,Exp[x]+ 1], {x, 0, Infinity}, GenerateConditions->None] == Log[2]
Successful Successful - Successful [Tested: 1]